A Gestão Pública com foco na qualidade e produtividade voltada às instituições Federais de Ensino Superior: um estudo direcionado à Universidade Federal do Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
Today much has been said about globalization and competitiveness in the world, the axis of this discussion a special focus has been given to the quality of public services to citizens. Management proposals have emerged to public organizations, including institutions of higher education. For some authors the improvement of the educational system as a whole, will provide the exercise of citizenship, since it is the big difference to sustainable development and ensuring the sovereignty of a nation ensuring the sovereignty of a nation. In order to investigate the importance of public administration combined with a quality program at the Federal University of Amazonas was carried out this work. The methodology used was based on the descriptive literature and research was conducted a brief review on the concepts of public administration. Addressed the quality management principles applied, analyzed the quality as a tool for improvement in public administration, and pointed out its features, advantages in application efficiency. Emphasizes the need to improve against the development of management models. Highlights the Public Management Program and its effect on Administration shows its contribution to rationalize and streamline the management in the Public Administration and how it can contribute to improving the image of public service when it comes to education. It concludes that the benefits can be significant, because it gives more reliability to the actions taken by public institutions, allocating more practice in implementing these services.
Keywords: Serviço Público; Programa de Qualidade; Instituições de Ensino Superior; Gestão Pública; Public Service; Quality Program; Higher Education Institutions; Public Management; ENGENHARIAS: ENGENHARIA DE PRODUÇÃO